Storage Time of Filtered Red Blood Cells and Post-Transfusion Complications (Review) - V. V. Moroz; E. A. Sherstyukova; E. K. Kozlova; V. A. Sergunova (Общая реаниматология, 2021)
Red blood cells are the most required blood transfusion products worldwide. Safety and efficacy of blood transfusion are still relevant issues. Clarification of the causes and mechanisms of post-transfusion complications requires additional research.Aim of the review is to summarize the data of clinical and research studies on transfusion of red blood cell suspension with various storage times.Material. We selected 76 sources from Web of Science, Scopus, and RSCI databases containing pertinent clinical and scientific research data, as well as blood transfusion guidelines.Results. We reviewed the main stages of preparation and storage of filtered red blood cells, described biochemical and structural alterations occurring during blood storage, summarized clinical data on post-transfusion complications, and analyzed clinical consequences and molecular structure abnormalities of red blood cells in relation to their storage time.Conclusion. During long-term storage, red blood cells undergo significant structural and metabolic changes. The clinical use of relatively «old» red blood cells increases the risk of post-transfusion complications. However, the pathophysiological differences between «young» and «old» erythrocytes remain unclear. Large clinical and molecular research studies may add to our understanding of the complex issues related to blood transfusion.